The spatio-temporal regulation of Polo-like kinase 1 in DNA repair - Legg, K (2019)
The G2/M cell cycle kinase Polo-like kinase 1 (PLK1) was recently discovered to play an active role in DNA repair by phosphorylating the RAD51 recombinase to aid homologous recombination. This occurs at a much shorter timeframe than the well-characterised downregulation of PLK1 activity via the DNA damage checkpoint. In this thesis, I expand upon this by investigating the regulation of PLK1 during this earlier timeframe post-damage. Laser microirradiation experiments observe fluorescently-tagged PLK1 localising to DNA damage sites within 15 minutes, in both S/G2 and, unexpectedly, G1 cells. In S/G2, this recruitment is dependent on PLK1's polo-box domain binding sites primed by the cyclin-dependent kinase CDK2. Activity of the DNA damage response kinase ATM is also required for PLK1's localisation to damage in both phases of the cell cycle. Meanwhile, a proteomics approach identified novel DNA repair-related PLK1 binding partners, including the E3 ubiquitin ligase UBR5 and the protein kinase DYRK2. DYRK2 increases in association with PLK1 within 30 minutes post-damage and can induce PLK1 activation by phosphorylation of its T-loop. These findings shed light onto how PLK1 is regulated to carry out its repair function, open up new avenues of future investigation into this topic, and even suggest the possibility of PLK1 playing further as-yet-uncharacterised roles in DNA repair.